PENGARUH MANAJEMEN LABA DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN - Sari, Handini Narati; Astuti, Titiek Puji; Suseno, Agus Endrianto (Widya Mandala Surabaya Catholic University, 2018)
The purpose of this study proves empirically the influence of earnings management and dividend policy on firm value. The earnings management variable is measured through a discretionary accrual using the modified Jones model, whereas the dividend policy is measured through the dividend payout ratio. This study also uses control variables such as leverage, profitability and firm size. The type of this research is comparative causal that explains the causal hypothesis between the variables. The population of this research includes all companies listed on the Indonesia Stock Exchange. The method to get samples used purposive sampling. Based on purposive sampling method, there are 79 companies meeting the criterias. Research period for 5 years, it is started from 2012 to 2016, so total sample used in this research as much as 395. This research uses panel data which applied with Eviews verse 9. The results showed that the independent variables and control variables have a significant influence on firm value except earnings management. The dividend policy has a positive effect. Control variables of leverage and profitability have a positive effect while firm size has a negative effect on firm value. The value of adjusted R squared is 82%. This can be interpreted that the independent variables are able to explain well the dependent variable